Congenital neurosyphilis in neonatal sepsis by Leclercia adecarboxylata: a case report - Tanaya, Putu Wahyu Dyatmika; Manuaba, Ida Ayu Sri Kusuma Dewi; Saputra, I Wayan Agus Gede Manik (Journal of Clinical Microbiology and Infectious Diseases, 2023)
Introduction: Sepsis remains a leading cause of morbidity and mortality in neonates. In accordance with the development of diagnostic testing, various pathogens have been found to cause neonatal sepsis, ranging from common to even rarer pathogens. Leclercia adecarboxylata is a Gram-negative bacillus rarely found in neonatal sepsis and was previously found predominantly in environmental settings and the human gastrointestinal tract as commensal bacteria. We describe a rare case of Leclercia adecarboxylata in neonatal sepsis with congenital neurosyphilis. Case Description: We present a male neonate born from a positive syphilis serological test mother, presented with sepsis manifestation. Blood culture reveals growth of Leclercia adecarboxylata. The patient received both therapeutic regimens of antibiotics for sepsis and congenital syphilis. The cerebrospinal fluid analysis also performed revealed suggestive of congenital neurosyphilis. The patient passed away due to multiple organ failure. Conclusion: Neonatal sepsis and congenital neurosyphilis present with identical manifestations; therefore, appropriate recognition and comprehensive management should be done